Pemanfaatan Profil Pelajar Pancasila untuk Membantu Siswa dalam Menelaah Teks Prosedur Bahasa Indonesia - Wulandari, Adellia Putri; Markhamah, Markhamah (Fakultas Sastra Universitas Muslim Indonesia, 2024)
The aim of this research is to explain the Profil Pelajar Pancasila (P3) used in learning procedural text analysis for class VII students at SMP Muhammadiyah 15 Wonoharjo. The research methodology integrates a qualitative approach with procedural elements. Two ways of collecting data other than tests are questionnaires and observation. The qualitative description method was used to test the data. The research conclusion shows that students appear to show a series of behaviors and characteristics that are in accordance with the P3 dimensions when they learn to interpret procedural texts. Learners demonstrate a series of behaviors and characters that are consistent with the P3 dimensions. Research findings show that students can effectively apply the P3 dimensions starting with the routine of worship and prayer, the ability to accept differences in perceptions and opinions, the ability to participate in small group discussions, the capacity for critical thinking and problem solving, and their ability to act independently and wisely as part of their responsibilities as students of Pancasila.